Phocoenamicins B and C, New Antibacterial Spirotetronates Isolated from a Marine Micromonospora sp. - Pérez-Bonilla, Mercedes (Mar Drugs, 2018)
Phocoenamicins B and C (1 and 2), together with the known spirotetronate phocoenamicin (3), were isolated from cultures of Micromonospora sp. The acetone extract from a culture of this strain, isolated from marine sediments collected in the Canary Islands, displayed activity against methicillin-resistant Staphylococcus aureus (MRSA), Mycobacterium tuberculosis H37Ra and Mycobacterium bovis. Bioassay-guided fractionation of this extract using SP207ss column chromatography and preparative reversed-phased HPLC led to the isolation of the new compounds 1 and 2 belonging to the spirotetronate class of polyketides. Their structures were determined using a combination of HRMS, 1D and 2D NMR experiments and comparison with the spectra reported for phocoenamicin. Antibacterial activity tests of the pure compounds against these pathogens revealed minimal inhibitory concentration (MIC) values ranging from 4 to 64 µg/mL for MRSA, and 16 to 32 µg/mL for M. tuberculosis H37Ra, with no significant activity found against M. bovis and vancomycin-resistant Enterococcus faecium (VRE) at concentrations below 128 µg/mL, and weak activity detected against Bacillus subtilis grown on agar plates.